A study on the influence of transmission errors on WLAN IEEE 802.11 MAC performance - Lopez-Aguilera, Elena; Casademont, Jordi; Villegas, Eduard Garcia (Wireless communications and mobile computing, 2011)
Since the advent of the first IEEE 802.11 standard for WLANs, several papers have been presented that evaluate the IEEE 802.11 DCF access method. In realistic WLAN environments frame errors usually occur due to non‐ideal channel conditions; in this way, papers including adverse transmission conditions in the evaluation have been published later in the literature. In this paper, we review existent analytical models that include the influence of transmission errors in IEEE 802.11 DCF performance. We modify current models and provide a more accurate analysis, thus allowing the evaluation in single rate and multi‐rate scenarios with stations subject to different link error conditions. Moreover, this paper exposes the unfairness problem that arises in IEEE 802.11 DCF networks with stations subject to different transmission conditions through analytical and simulation results. Stations are not able to distinguish collisions from failed transmissions due to link errors; both result in a missing ACK and, consequently, the transmitting stations apply the exponential backoff algorithm. This fact leads to a lower performance for stations in worse transmission conditions. Copyright © 2010 John Wiley & Sons, Ltd. In this paper, we review existent analytical models that include the influence of transmission errors in IEEE 802.11 DCF performance. We modify current models and provide a more accurate analysis, thus allowing the evaluation in single rate and multirate scenarios with stations subject to different link error conditions. Moreover, this paper exposes the unfairness problem that arises in IEEE 802.11 DCF networks with stations subject to different transmission conditions through analytical and simulation results.